Gilgameş Destanı’ndan Hareketle Sümer Kentini Okumak. - Kaya, Ece; Şafak, Gökçe Nur (Electronic Turkish Studies, 2020)
Man, who built the cities which are regarded as the beginning of civilization through the transition to permanent settlement, has shaped his space he lived in and was also shaped by these spaces. It is possible to see this mutual relationship in the archeological findings and various works left behind by civilizations. As Göbeklitepe and Çatalhöyük remain the first settlements of the civilization, the archaeological findings obtained from these settlements is not suitable-holistically or integrally-to understand the civilizations and settlements of the period. However, the Sumerian civilization called “the land of written texts” and therefore its cities seems appropriate to review in an integrated manner. In this study, an evaluation of Sumerian city was carried out by using the Epic of Gilgamesh. The reason for starting from the Epic of Gilgamesh in the study is because literary works may harbor clues about the mindset of the era and at the same time and it also contains important data related to the social, political, religious, economic, artistic, cultural structure and life of that era. When the Sumerian written works were found, it was seen that some of these works, structures and the mythology of this civilization was not limited to only their era, but they also have influence on successor civilizations in such a manner that the traces can be found even today. Understanding the Sumerian city which is one of the oldest city experience known in history, will contribute understanding the internal dynamics of today's urban life. In this study, an analysis of the administrative, economic and socio-cultural structure of the Sumerian civilization has been obtained and a vision has been reached regarding the Sumerian city from the Epic of Gilgamesh by using the descriptive analysis method. A holistic approach was used to evaluate various structures and institutions such as temples and palaces in Sumerian cities and a portrait is drawn regarding the relationship between the intellectual structure of the period and the city. Traces of the transition from tribal societies to urban life was followed in the primary examples in Sumerian mythology. A conclusion was reached that the fate of the city and Gilgamesh are parallel and the processes of transition from tribal society to urban society are intertwined with the initiation of Gilgamesh. In the process of civilization of Enkidu, it can be observed that taking nature under control by taming and the importance given by Sumerians to urban values. It was seen that the legitimacy of the ruling power of kings and temple was divinity and sanctity which determined the prominent structures and institutions in the city. Finally, the similarities of some themes referring to cities that we found in the Sumerian cities which can be described as a symbol of the cosmos on earth, with other cities are emphasized. The universality of urban-rural/nature perceptions of civilizations and cosmogonic references of cities were pointed out. This universality is indicated by showing important examples of similarities in Ancient Greek and Turkish mythologies.